Long-term Prognosis Following Vascular Graft Infection: A 10-Year Cohort Study. (1st February 2022) - Sixt, Thibault; Aho, Serge; Chavanet, Pascal; Moretto, Florian; Denes, Eric; Mahy, Sophie; Blot, Mathieu; Catherine, François-Xavier; Steinmetz, Eric; Piroth, Lionel
Abstract: Background: Vascular graft infection (VGI) remains a severe disease with high mortality and relapse rates. We performed a retrospective single-center cohort study to highlight factors associated with long-term all-cause mortality in patients with vascular graft infection. Methods: All patients hospitalized in our facility over 10 years for VGI were included. VGI was defined by the presence of a vascular graft or an aortic stent graft (stent or fabric), associated with 2 criteria among clinical, biological, imaging, or microbiological elements in favor of VGI. The primary outcome was all-cause mortality. Empirical antibiotic therapy was considered as appropriate when all involved pathogens were susceptible in vitro to the antibiotics used. The surgical strategy was defined as nonoptimal when the graft was not removed in a late-onset surgery (>3 months) or no surgery was performed. Results: One hundred forty-six patients were included. Empirical antibiotic therapy was administered in 98 (67%) patients and considered appropriate in 55 (56%) patients. Surgery was performed in 136 patients (96%) and considered as optimal in 106 (73%) patients. In multivariable analysis, appropriate empirical antibiotic therapy was associated with a lower probability of mortality (hazard ratio, 0.47 [95% confidence interval, .30–.79]; P = .002). Long-term survival did not differ according to whether the surgical strategy was considered optimal or not (log-rank = 0.66). Conclusions: Appropriate empirical antibiotic therapy is a cornerstone of the management of VGI. Whenever possible, antibiotics must be associated with optimal surgical management. However, surgery could potentially be avoided in comorbid patients who are treated with appropriate antibiotics. Abstract : Appropriate empirical antibiotic therapy for vascular graft infection is associated with better survival. Long-term survival does not differ whether or not the surgical strategy is considered optimal. Efficient antibiotic treatment may help to avoid surgery for patients with comorbidities, without causing long-term excess mortality.